Prevalence of self-reported food allergies among the Saudi population and investigation of the challenges faced by people with food allergy: A cross sectional online survey-based study - Zaher, Sara; Bookari, Khlood; Arrish, Jamila; Alnafisah, Ruyuf; alobaid, Rawan; Albuayjan, Norah; Binammar, Albandari; Alsayegh, Abdulrahman; A. Abduljawad, Eman; A. Halawani, Reham; M Alkhalaf, Majid; Al-Otaibi, Hala (Progress in Nutrition, 2023)
Background: The topic of food allergy (FA) is widely studied and investigated in developed countries. However, there are lack of published reports concerning FA prevalence in the middle-east region including Saudi Arabia (KSA).  Therefore, we aimed to assess the prevalence of FA among children and adults in KSA and to identify the most common types of FAs.Methodology: An online survey was distributed to collect information about the prevalence of self-reported FA, type of FA and challenges faced by food allergic people.Results: We received 15142 responses of those 3237(21%) subjects were diagnosed with FA or taking care of someone with FA. About 15% of food allergic subjects were ≥18 years and 6.4% were